The clinical utility of serum tartrate‐resistant acid phosphatase 5b in the assessment of bone resorption in patients on peritoneal dialysis. (6th April 2013) - Yamada, Shunsuke; Tsuruya, Kazuhiko; Yoshida, Hisako; Taniguchi, Masatomo; Haruyama, Naoki; Tanaka, Shigeru; Eriguchi, Masahiro; Nakano, Toshiaki; Kitazono, Takanari
Summary Objectives Serum tartrate‐resistant acid phosphatase 5b (TRACP5b) is a bone resorption marker used in the assessment of bone metabolic status. The present study was designed to determine the clinical characteristics and utility of measuring serum TRACP5b levels in peritoneal dialysis (PD) patients. Design Cross‐sectional study. Patients Forty‐one patients receiving PD treatment in a single centre. Measurement Serum levels of the bone turnover markers TRACP5b, N‐terminal cross‐linking telopeptide of type 1 collagen (NTX), bone‐specific alkaline phosphatase (BAP), and parathyroid hormone (PTH) were simultaneously measured. The correlation of serum TRACP5b with other established bone markers was analysed after logarithmic transformation. Multivariate linear regression analysis was performed to examine the effects of both renal and peritoneal Kt/V (an index for solute clearance) for urea on bone markers using age, sex, body mass index, and PTH as covariates. Bone markers were also measured in three patients before and after treatment with cinacalcet hydrochloride, alphacalcidol, and raloxifene hydrochloride. Results Log TRACP5b was significantly correlated with log NTX, log BAP and log PTH. In the multivariate analysis, peritoneal Kt/V was not correlated with log NTX, log BAP or log TRACP5b. In contrast, renal Kt/V was significantly correlated with log NTX only. Responses to drug treatment were more accurately determined from serum TRACP5b and BAP than from serum NTX. Conclusions Serum TRACP5b and BAP are potentially useful biomarkers for the evaluation of bone turnover in PD patients because they correlate well with other established bone markers and they are not influenced by renal and peritoneal clearances.